2022
DOI: 10.1152/ajplung.00341.2021
|View full text |Cite
|
Sign up to set email alerts
|

µCT to quantify muco-obstructive lung disease and effects of neutrophil elastase knockout in mice

Abstract: Muco-obstructive lung diseases are characterized by airway obstruction and hyperinflation, which can be quantified by imaging. Our aim was to evaluate µCT for longitudinal quantification of muco-obstructive lung disease in β-epithelial Na+ channel overexpressing (Scnn1b-TG) mice and of the effects of neutrophil elastase (NE) knockout on its progression. Lungs from wild-type (WT), NE-/-, Scnn1b-TG, and Scnn1b-TG/NE-/- mice were scanned with 9 µm resolution at 0, 5, 14 and 60 days of age, and airway and parenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…For the mean airspace diameter in the βENaC-Tg lungs, we did not find any publication addressing exactly the same age group as in our paper. However, the data published for MLI for days 14 and 60 are 75 and 80 µm, which is comparable to our results for day 36 (78.75 ± 2.9 µm) [57].…”
Section: Discussionsupporting
confidence: 91%
“…For the mean airspace diameter in the βENaC-Tg lungs, we did not find any publication addressing exactly the same age group as in our paper. However, the data published for MLI for days 14 and 60 are 75 and 80 µm, which is comparable to our results for day 36 (78.75 ± 2.9 µm) [57].…”
Section: Discussionsupporting
confidence: 91%
“…Our data show that MMP-9 deficiency does not ameliorate the emphysema phenotype of βENaC-Tg mice, which is characterized by an increased lung volume, distal airspaces enlargement and destruction of alveolar septa on histology. In contrast, previous studies found that NE is an important effector molecule of these processes [ 6 , 7 , 9 , 39 , 48 ]. In these studies, genetic deletion of NE ameliorated the emphysematous lung morphology of βENaC-Tg mice, however, the effects on lung mechanics have not been investigated so far [ 9 , 39 ].…”
Section: Discussionmentioning
confidence: 62%
“…In contrast, previous studies found that NE is an important effector molecule of these processes [ 6 , 7 , 9 , 39 , 48 ]. In these studies, genetic deletion of NE ameliorated the emphysematous lung morphology of βENaC-Tg mice, however, the effects on lung mechanics have not been investigated so far [ 9 , 39 ]. To further substantiate the differential roles of NE vs. MMP-9 in emphysema formation, we performed invasive lung function testing as a sensitive tool to compare the effects of genetic deletion of NE vs. MMP-9 on lung mechanics in βENaC-Tg mice.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations